2011
DOI: 10.4269/ajtmh.2011.10-0676
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Loop-Mediated Isothermal Amplification (LAMP) for Malaria Diagnosis in a Field Setting

Abstract: We used the loop-mediated isothermal amplification (LAMP) method developed by our group for malaria diagnosis with genus-specific and species-specific primers for the four human malaria parasites at a field clinic in comparison with standard microscopy. Among 110 blood samples collected from the malaria clinic in Thailand, LAMP detected 59 of 60 samples positive by microscopy (sensitivity = 98.3%) and none of the 50 microscopy-negative samples (specificity = 100%). Negative predictive value (NPV) and positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 16 publications
4
52
0
Order By: Relevance
“…The use of the simple boiling method for template preparation provides a good alternative to conventional (expensive and labor-intensive) DNA extraction methods, which might not always be possible in the field. In this study, we were able to successfully use heat-treated samples for LAMP amplification, similar to results reported by Sirichaisinthop et al, Lucchi et al, and Tao et al (28,33,34). As such, the rapid boiling method for extracting DNA from filter paper is favorable for LAMP.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…The use of the simple boiling method for template preparation provides a good alternative to conventional (expensive and labor-intensive) DNA extraction methods, which might not always be possible in the field. In this study, we were able to successfully use heat-treated samples for LAMP amplification, similar to results reported by Sirichaisinthop et al, Lucchi et al, and Tao et al (28,33,34). As such, the rapid boiling method for extracting DNA from filter paper is favorable for LAMP.…”
Section: Discussionsupporting
confidence: 72%
“…The method had initially been applied in malaria diagnosis on a small scale at a field clinic in an area in Thailand where malaria is endemic by using a simple boiling method for DNA extraction to simplify template preparation (28). This preliminary study demonstrated that LAMP showed sensitivity, specificity, PPV, and NPV comparable to those of microscopy, a reference method.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations